2013
DOI: 10.1097/jto.0b013e318294c909
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Volume Decrease at 8 Weeks Is Associated with Longer Survival in EGFR-Mutant Advanced Non–Small-Cell Lung Cancer Patients Treated with EGFR TKI

Abstract: Background The study investigated if tumor volume changes at 8 weeks of therapy are associated with outcomes in advanced NSCLC patients with sensitizing EGFR mutations treated with EGFR tyrosine kinase inhibitors (TKIs). Patients and methods In 56 advanced NSCLC patients with sensitizing EGFR mutations treated with first-line erlotinib or gefitinib, tumor volumes of dominant lung lesions were measured on baseline and follow-up CT and were analyzed for association with survival. Results Among 56 eligible pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 54 publications
7
82
1
2
Order By: Relevance
“…A small study of 13 patients with resectable locally advanced NSCLC found that both pre- and post-treatment gross tumor volume predicted PFS [27], using automatic deformable image registration software for volumetric measurements. Nishino et al evaluated a group of 56 NSCLC patients with EGFR mutations treated with first-line tyrosine kinase inhibitors [28] and similar to our results found that an early decrease in tumor volume was associated with overall survival.…”
Section: Discussionsupporting
confidence: 86%
“…A small study of 13 patients with resectable locally advanced NSCLC found that both pre- and post-treatment gross tumor volume predicted PFS [27], using automatic deformable image registration software for volumetric measurements. Nishino et al evaluated a group of 56 NSCLC patients with EGFR mutations treated with first-line tyrosine kinase inhibitors [28] and similar to our results found that an early decrease in tumor volume was associated with overall survival.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, an 8-week time point has been previously studied to identify early markers for outcome in advanced NSCLC patients. (3133)…”
Section: Resultsmentioning
confidence: 99%
“…As tumor volume has also been shown to be a reproducible marker to characterize tumor response and progression and predict survival for advanced NSCLC treated with molecular targeted therapy including EGFR inhibitors(33,35,36), the utility of tumor volume in the setting of immune-related response evaluations can be tested in future studies. The response assessment of irRECIST is based on the sum of the target lesion measurements in each patient, and does not reflect different behaviors of individual lesions in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations are consistent with these findings and those demonstrated in other malignancies treated with targeted therapy, including KRAS wild-type metastatic colorectal cancer and advanced non-small cell lung cancer, in which early tumor shrinkage has been shown to be a powerful predictor of outcome. [10, 11] Compared to previously published studies in mRCC, our study has many novel aspects. This is the first and largest comprehensive study demonstrating that the best tumor response on imaging is an independent prognostic factor for survival in mRCC, irrespective of line of treatment or agent applied.…”
Section: Discussionmentioning
confidence: 99%